Peran Pendidikan Terhadap Perubahan Sosial di Sekolah SMAN 1 Tenggarong Seberang: PAI - Kurnia Wati, Mega; Fatimatul Khoiriyah , Binti; Yasin, Muhammad (Yayasan Literasi Sains Indonesia, 2023)
Education and social change are two things that are related to each other and cannot be separated. Education is an institution that can be used as an agent of social change and at the same time can determine the direction of social change which is called development in society. The research objective is to find out the role of education in social change and the process of the impact of social change. The focus of this research is what is the role of education in social change and how is the process of the impact of social change. The method used by researchers is a qualitative research method with a descriptive type that collects data from interviews, documentation, and field observations. The results of this study that 1). The role of education towards social change in schools is to be able to create a lot of interaction and character building which is very necessary so that it is very beneficial for future generations 2). The impact on human life, technological changes that occur can make it easier for people such as teachers and students to find information with a lot of time, even searching for information can be done anywhere and anytime and social changes can make it easier to process data and school grades to help developers due to technological advances.